2012
DOI: 10.1111/j.1747-0285.2012.01428.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of FDA‐approved Drugs that Computationally Bind to MDM2

Abstract: The integrity of the p53 tumor suppressor pathway is compromised in the majority of cancers. In 7% of cancers, p53 is inactivated by abnormally high levels of MDM2—an E3 ubiquitin ligase that polyubiquitinates p53, marking it for degradation. MDM2 engages p53 through its hydrophobic cleft and blockage of that cleft by small molecules can re-establish p53 activity. Small molecule MDM2 inhibitors have been developed, but there is likely to be a high cost and long time period before effective drugs reach the mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
19
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 39 publications
8
19
0
3
Order By: Relevance
“…22 Since the submission of this manuscript a crystal structure of TASK-1, bound to inhibitory compounds, was released. Consistent with previously published work, 20,22,40,41 L122 and L239, along with some other amino acids, were important for binding and trapping of these inhibitory compounds, within TASK-1 channels. For two novel inhibitory compounds (BAY 1000493 and BAY 2341237) it was shown that the compounds bind within an inner vestibule, directly below the selectivity filter.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…22 Since the submission of this manuscript a crystal structure of TASK-1, bound to inhibitory compounds, was released. Consistent with previously published work, 20,22,40,41 L122 and L239, along with some other amino acids, were important for binding and trapping of these inhibitory compounds, within TASK-1 channels. For two novel inhibitory compounds (BAY 1000493 and BAY 2341237) it was shown that the compounds bind within an inner vestibule, directly below the selectivity filter.…”
Section: Discussionsupporting
confidence: 90%
“…By truncating the channel, it is possible that the channel has been pushed into an open state, perhaps by locking the channel into a particular phosphorylation state, or because gating at the selectivity filter is disrupted by C-terminus truncation. 22 This correlates with another previous molecular modelling study of doxapram, which suggests the drug has a high affinity for a hydrophobic cleft in which to bind 40 and with a study conducted on TASK-3_L122D, which suggested that mutating this amino acid to an aspartate produces a fixed open conformation that reduces the effects of anaesthetics. 37,38 Surprisingly, however, truncation of murTASK-3 channels, resulted in a significant reduction in current recorded through these channels, but this still attenuated the effect of doxapram.…”
Section: Discussionsupporting
confidence: 83%
“…Many efforts for computationally predicting drug-target interactions exist, spanning both chemo-centric [7, 8] and target-based methodologies [9, 10]. Chemo-centric approaches utilize physical and chemical information obtained from ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Chemo-centric approaches utilize physical and chemical information obtained from ligands. Some approaches relate receptors based on the chemical similarity [7] as well as shape similarity [8] between ligands. Large public databases that aid in extracting ligand-based data for informatics also exist [9].…”
Section: Introductionmentioning
confidence: 99%
“…The p53-binding part of MDM2 is rigid, and its solved structure is widely used in molecular docking studies. 13 Most of the MDM2 inhibitors mimic the structure of the TAD1 α-helix 14 and hence form the same intermolecular contacts with the hydrophobic MDM2 pocket as the original p53. An alternative concept of stapled peptides was shown to be a successful strategy in attempts to inhibit MDM2.…”
mentioning
confidence: 99%